Problem-oriented programming of regional SME development in the eurointegration process based on the quantified SWOT analysis - Antoniuk, Dmitro; Antoniuk, Katerina (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The purpose of the article is to develop the strategic directions of SMEs modernization in the Zaporizhzhya region.Design/methodology/approach. The systemic, institutional approaches, the methodology of constructing a quantified matrix of SWOT analysis of SMEs in the region were used in the article.Findings. The imperfection of the institutional structure of entrepreneurship development in the process of European integration of Ukraine in the program documents of the national and regional levels has necessitated the development of strategic goals, priorities and tasks for the modernization of SMEs in the region. According to the results of the study: the matrix SWOT-analysis of SMEs in the region, supplemented by a quantified analysis of the isolation of groups of threats and weaknesses of entrepreneurship was proposed; dangerously weaknesses and dangerous threats, orientation of strategic directions for business development in the region was defined; problem-oriented measures “problems tree” and “decisions tree” of SME sector development in the region in the process of European integration was formulated.Research limitations/implications. The paper provides the directions for design an institutional basis for the modernization of the SME in the region.Originality/value. The scientific significance of the work is to study problem-oriented targets for strategic programming of structural changes derived from the modified SWOT analysis method, the development of a “problems tree” and a “decisions tree”. The main problems of SMEs in the region (lack of financial and credit resources and underdeveloped infrastructure of entrepreneurship) and ways to solve them (increasing the index of human development, reducing the impact of informal infrastructure, using modern technologies of resource-efficient and clean production, attracting international technical assistance resources, preparing public-private partnership projects) were identified.